1998
DOI: 10.1677/joe.0.1580341
|View full text |Cite
|
Sign up to set email alerts
|

Induction of osteoclast formation by parathyroid hormone depends on an action on stromal cells

Abstract: It is believed that parathyroid hormone (PTH) increases the resorptive activity of pre-existing osteoclasts through a primary interaction with cells of the osteoblastic lineage. Much less is known, however, of the mechanisms by which PTH induces osteoclast formation. It is known that osteoclast formation occurs through a contact-dependent interaction between stromal cells and haemopoietic precursors, but it is not known whether PTH acts on stromal cells or precursors to induce osteoclast formation. To address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 50 publications
0
13
1
Order By: Relevance
“…Additional soluble RANKL in this system was also enough to promote TRAP-positive cells to a similar extent as that induced by PTHrP. In contrast to our results, Fuller et al reported no additive effect with the combination of PTHrP and RANKL on osteoblasts, 34 but in the present study with cementoblasts, this combination significantly increased the number of TRAPpositive multinucleated osteoclasts in co-culture.…”
Section: Discussioncontrasting
confidence: 81%
“…Additional soluble RANKL in this system was also enough to promote TRAP-positive cells to a similar extent as that induced by PTHrP. In contrast to our results, Fuller et al reported no additive effect with the combination of PTHrP and RANKL on osteoblasts, 34 but in the present study with cementoblasts, this combination significantly increased the number of TRAPpositive multinucleated osteoclasts in co-culture.…”
Section: Discussioncontrasting
confidence: 81%
“…In contrast, most of the literature agrees that osteoclasts and their precursor cells lack high-affinity PTH receptors. (3,(6)(7)(8) Therefore, it has been proposed that the effects of PTH on osteoclasts are indirect. (9) The PTH receptor on target cells is activated by the binding of PTH or PTHrP.…”
Section: Introductionmentioning
confidence: 99%
“…In bone, the PPR is primarily expressed in osteoblasts, osteocytes and bone marrow stromal cells such as osteoblast precursor cells. Osteoclasts do not express the PPR, as demonstrated by the lack of response to PTH [22]. The actions of PTH and PTHrP in osteoclasts are mediated by osteoblasts and osteocytes responsible for secretion of factors that activate osteoclasts.…”
mentioning
confidence: 99%